Peran Moderasi Koneksi Politik dalam Pengaruh Multinasionalitas terhadap Penghindaran Pajak - Widya Cita Pramesti; Tasyahadul Fadlatil Laili (Universitas Muhammadiyah Malang, 2024)
Purpose: Tax avoidance is still commonly practiced by multinational corporations. The upper echelon theory considers top management as the most important strategic decision-maker and has a direct impact on organizational results, so it is suspected that political connections will affect tax avoidance by companies. This research aims to examine the moderating role of political connections in moderating the influence of multinationality on tax avoidance. Methodology/approach: This research uses a quantitative approach with a positivism paradigm. The sample for this research was chosen using the purposive sampling method. The sample in this research was 84 manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The data analysis technique used is Moderated Regression Analysis (MRA) with Stata 15 software. Findings: The research results show that multinationality has a positive effect on tax avoidance and political connections weaken the relationship between multinationality and tax avoidance. Practical and Theoretical Contribution/Originality: This research is expected to provide information for the Directorate General of Taxation as a reference to assess the tax avoidance behavior conducted by multinational companies in order to prevent fraud in taxation practices. Additionally, this research can contribute to the upper echelon theory in understanding the political connections that can moderate the relationship between multinationality and tax avoidance. Research Limitation: The use of a common tax avoidance measurement, namely the Effective Tax Rate (ETR). ETR only reflects the final result of tax avoidance, which can also be influenced by other factors such as regulations or the company's financial condition.